Endovascular treatment versus bypass in long SFA atherosclerotic lesions: a non-randomized comparative study - Yousry, Marwan; Fathy, Khaled Tarek; Afify, A. Gamal; Hafez, Ahmed Mohsen; Taha, Ahmed.A. (South Eastern European Journal of Public Health, 2025)
Background: The TransAtlantic Inter-Society Consensus (TASC II) classification categorizes superficial femoral artery (SFA) lesions. This study compares endovascular therapy and bypass surgery for treating challenging TASC II C and D SFA lesions, which are typically complex and involve severe disease. Purpose: the aim is to compare the outcome of endovascular interventions versus surgical bypass in treatment of superficial femoral artery atherosclerotic TASC II C&D lesions in patients with critical limb ischemia in terms of patency and limb salvage within one year follow up. Patients and methods: our study included 41 patients in bypass group (groub A) and 74 patients in endovascular group (groub B) with atherosclerotic TASC II C&D SFA lesion. Patients with non-salvageable limbs, acute ischemia, trauma, aneurysms, connective tissue disorders and arteritis were excluded. All patients had Rutherford 4 to 6. Saphenous vein and synthetic grafts were used in bypass group. POBA, DCB and stents were used in endovascular group. The patients were followed up for 1 year. Results: mean Patients’ age was 63.15 years in endo group and 58.76 years in bypass group, male 78.4% in endo group and 85.4% in bypass group. Patients’ presentation was incapacitating claudications, rest pain, minor tissue loss, and major tissue loss. Technical success achieved in 100% in bypass cases and 95.9%in endo group. 1ry patency rate was 71.4% in the bypass group versus 57.6% in the endo group, still not significant statistically (p-value 0.171). The assisted 1ry patency was 77.1% in bypass group and 83.3% in the endo group,.(p.value 0.449) 2ry patency rates was 82.9% and 89.4% in bypass and endo groups respectively. Our 1-year limb salvage rates were 85% in the bypass group versus 91.7%, the rate was better in the endo group but with statistically insignificant p.value between them (p: 0.343). The rate of reintervention was higher in endo group (31.8%) than bypass group (11.4%) which was statistically significant, (p.value 0.024). Overall mortality during follow up was only 1 patient in the bypass group (2.4%). the bypass group had higher complication rate (41.5%) than the endovascular group (12.2%) with statistically significant (p.value <0.001). Conclusion: Bypass surgery and endovascular management have comparable short terms outcomes in terms of patency and limb salvage in treating long SFA atherosclerotic lesion TASC II C&D. Rate of reintervention is higher with endovascular strategy. However, with lower morbidity and mortality compared with surgery.